RIB GRAFT RHINOPLASTY FOR DEPRESSED DORSUM OF NOSE - Tahir, Muhammad; Sabir, Salman; Ullah, Fahim (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the results of the technique of Costochondral rib graft Rhinoplasty in patients with depressed dorsum of nose. Material and Methods: This study was conducted in the Plastic Surgery Unit of PGMI, HMC from February 1997 to December 2002. It included all the patients with depressed dorsum of nose undergoing rib graft Rhinoplasty. A thorough history and physical examination with emphasis on the nasal deformity both from functional and cosmetic aspect was carried out. Both open and closed techniques of Rhinoplasty were employed. Photographs in standard frontal, lateral and worms eye view were taken. Record of patient's presenting complaints, patient's hopes and expectations, postoperative complications, patient satisfaction from cosmetic and functional point of view was made. Results: During this period, 42 patients underwent procedure of rib graft Rhinoplasty. Male-female ratio was 1:1.1. Mean age for men was 31 years and for females was 25 years. Causative factors for depressed nose were trauma in 33(78%), congenital in 4 (9.5%), infection in 3 (7.1%) and Wegener's syndrome in 2 (4.7%) patients. Patient satisfaction was achieved in 28(66%) patients, 11(28.1%) had partly acceptable result while 3(7.1%) were not satisfied with the result. One patient had pressure ulceration at the bridge of the nose and one had undue elevation of nasal tip due to fibrosis. There were no significant long-term donor area complications. Conclusion: Costochondral rib graft Rhinoplasty for depressed bridge of the nose is a safe option with minimal complications.